Analisis Pengaruh Earning Per Share (EPS), Return On Assets (ROA), dan Debt To Equity Ratio (DER) Terhadap Harga Saham (Studi Kasus Perusahaan Yang Terdaftar Pada Indeks Emiten LQ 45 Tahun 2010-2014 - Hartadi, Tri; , Imron Rosyadi, SE, M.Si (2016)
The purpose of this study was to measure the effect of Earning Per Share (EPS), Return on Assets (ROA), and Debt To Equity Ratio (DER) to the price of shares in companies listed on LQ 45 listed on the Stock Exchange in 2010-2014. The data used is secondary data in the form of financial statements of companies acquired from the Indonesian Capital Market Directory (ICMD) and also www.idx.co.id. In determining this sample using purposive sampling method of determining the sample based on certain criteria. Data analysis method used is multiple linear regression analysis and hypothesis testing using t-statistic, the F-statistic, and the coefficient of determination. From the analysis during the study period t test is to determine the effect of independent variables individually against the dependent variable showed variable Earning Per Share (EPS) significantly affect the stock price, as well as variable Return On Asset (ROA), and Debt To Equity ratio (DER) as a result of less than 0.05 means Ho rejected. While the F-test is used to determine the effect Earning Per Share (EPS), Return on Assets (ROA), and Debt To Equity Ratio (DER) simultaneously to the stock price shows that F count equal to 112.009 with sig. 0.000 less than 0.05 means Ho rejected and independent variables simultaneously significant positive effect on stock prices. While the determinant coefficient test is used to determine how much the ability of independent variables in explaining the dependent variable. The results of the data analysis menujukakan Earning Per Share (EPS), Return on Assets (ROA), and Debt To Equity Ratio (DER) partially affect stock prices. The determinant of coefficient test concluded that the dependent variable can be explained by the independent variables of 86.88%, and the remaining 13.2% is influenced by other factors beyond the variables studied. Results of this study was successful because of the independent variables can explain the dependent variable of more than 50%